The Role of Motivation and Organizational Commitment on Employee Performance - Parandy, La Mema (Journal of Social Science and Business Studies, 2024)
This study aims to examine the influence of motivation and organizational commitment on employee performance. The researcher conducted this study at the Blood Donor Unit of the Indonesian Red Cross in Surabaya City. The study population included all 132 permanent employees, with a sample size of 57 people. Researchers gathered data from existing literature and secondary sources. The researcher carried out the data analysis using the partial least squares (PLS) technique with Smart PLS software version 2.0. The test results revealed that motivation can enhance employee performance by addressing physiological needs, security needs, and appreciation needs. This occurs when employees receive recognition from superiors for their completed work, thereby fostering a sense of self-actualization and progress in task implementation and completion. Organizational commitment doesn't significantly influence employee performance, and we need to enhance the indicators of organizational commitment, which include affective aspects such as building relationships, continuous aspects like persevering and increasing participation, and normative aspects like confidence and pride.